Advances in imaging and electron physics. - Hawkes, P. W. (Advances in imaging and electron physics ;, 2017)
Advances in Imaging and Electron Physics, Volume 203, merges two long-running serials, Advances in Electronics and Electron Physics and Advances in Optical and Electron Microscopy. It features extended articles on the physics of electron devices (especially semiconductor devices), particle optics at high and low energies, microlithography, image science, digital image processing, electromagnetic wave propagation, electron microscopy, and the computing methods used in all these domains.